Effects Of n-Butanol Blends On The Formation Of Hydrocarbons And PAHs From Fuel-Rich Heptane Combustion In A Micro Flow Reactor With A Controlled Temperature Profile - Mohd Hanafi, Mohd Hafidzal; Nakamura, Hisashi; Hasegawa, Susumu; Tezuka, Takuya; Maruta, Kaoru (Taylor & Francis Group, 2020)
The effects of the addition of n-butanol on the formation of hydrocarbons and polycyclic aromatic hydrocarbons (PAHs) of n-heptane combustions were investigated using a micro flow reactor (MFR) with a controlled temperature profile. The concentrations of small and large hydrocarbons, as well as PAHs were measured at a maximum wall temperature of 1,100 K and atmospheric pressure. The values obtained from several mechanisms were compared to the measurement values at equivalence ratios of 2.0–5.0. The CRECK mechanism was in fair agreement with the measurements. The computational results confirmed that the concentration of the PAHs and soot precursors’ decreased, while that of CO and CO2 increased due to the addition of butanol. These trends were also shown by the measurement values. The reaction path and rate of production analyzes were carried out to identify the major reactions contributing toward species concentrations.